Adoption of Electronic Marketing Tools in the Nigerian Construction Industry - Tolulope S. FAWALE; Monday O. IMAFIDON; Chukwuemeka P. OGBU (UNIABUJA Journal of Engineering and Technology (UJET), 2025)
There is a growing trend of e-marketing tools which have been enhanced by internet penetration in the Nigerian construction industry. To promote construction services through e-marketing tools, there is the need to address the concerns of firms on what is required to engage effectively with stakeholders. The study therefore assessed the perspectives of construction professionals on the level of awareness and frequency of use of e-marketing tools in Edo State, Nigeria. Respondents were selected from construction professionals who are involved in pre-design, design and construction phases of projects in Edo State. With the aid of a structured questionnaire, data were collected and analysed using tables, percentages and mean scores. The study found out that the level of awareness of professionals was high on e-marketing tools like WhatsApp (MS= 4.08), YouTube (MS=3.88) and E-mail (MS= 3.85) but low on Mobile monkey (MS=1.53), Hootsuite (MS=1.45) and Trello (MS=1.33). Conversely, E-mail, Facebook and WhatsApp accounted for 100% usage on the frequency of use of e-marketing tools by construction professional. Hence, the study concluded that the greater the level of awareness of e-marketing tools, the higher their frequency of use in construction projects. It is essential to simultaneously improve awareness and use of the e-marketing tools due to their relevance in construction projects. The study recommended that construction consultants should encourage bidders on the use of e-marketing tools for construction project management, while government should prioritise continuous investment in internet connectivity, power and digital infrastructure to support the growth of e-marketing.